Stability investigations of cageless ball bearings considering balls and outer rings with variable diameter raceways - Jingwei Zhang; Yanling Zhao; Xiaonan Zhang (Advances in Mechanical Engineering, 2022)
The reducer raceway in the inner raceway of the outer ring of the cageless bearing can effectively make the rolling automatically discrete; nevertheless, it is unclear how this impacts the rolling. This work examines the influence of three types of reducer raceway structure form and prevent position on the mutual discrete stability of rolling bodies using numerical simulation and experiment. By analyzing the phase diagrams of rolling body velocity-displacement and inner ring velocity-displacement, it is discovered that the bearing area increases the stability of a single elliptical or shuttle-shaped local reducer raceway. The vibration of the elliptical reducer raceway bearing is the smallest and the rolling body discrete is the most stable, as determined by vibration testing of three forms of single reducer raceway ball bearings under varied working situations.